2022
DOI: 10.1038/s41467-022-34815-3
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation-based classification of sinonasal tumors

Abstract: The diagnosis of sinonasal tumors is challenging due to a heterogeneous spectrum of various differential diagnoses as well as poorly defined, disputed entities such as sinonasal undifferentiated carcinomas (SNUCs). In this study, we apply a machine learning algorithm based on DNA methylation patterns to classify sinonasal tumors with clinical-grade reliability. We further show that sinonasal tumors with SNUC morphology are not as undifferentiated as their current terminology suggests but rather reassigned to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 58 publications
1
22
0
1
Order By: Relevance
“…Während Datensätze aus herkömmlichen NGS-Panels, die heutzutage in der Routinediagnostik zur Identifizierung einzelner Mutationen verwendet werden, mit klassischen Datenanalyse-Strategien gehandhabt werden können, profitieren hochdimensionale Genomik-und Proteomik-Datensätze von Verfahren des maschinellen Lernens. Sie helfen dabei die Dimensionalität zu reduzieren und heterogene Datenarten, wie Genregulationen in Netzwerken oder DNA-Methylierungsdaten zu integrieren [49,50,51,52].…”
Section: Künstliche Intelligenz Zur Bewältigung Der Datenmengenunclassified
“…Während Datensätze aus herkömmlichen NGS-Panels, die heutzutage in der Routinediagnostik zur Identifizierung einzelner Mutationen verwendet werden, mit klassischen Datenanalyse-Strategien gehandhabt werden können, profitieren hochdimensionale Genomik-und Proteomik-Datensätze von Verfahren des maschinellen Lernens. Sie helfen dabei die Dimensionalität zu reduzieren und heterogene Datenarten, wie Genregulationen in Netzwerken oder DNA-Methylierungsdaten zu integrieren [49,50,51,52].…”
Section: Künstliche Intelligenz Zur Bewältigung Der Datenmengenunclassified
“…They also reported that IDH2 -mutated tumors are associated with a worse outcome, which is different from what had been published in the literature beforehand [ 25 , 36 ] and larger studies are required to confirm these findings. Having said this, their reported association of IDH2 -mutation as well as SMARCB1 deficiency with aberrant global methylation was later confirmed by a very recent large methylation study on sinonasal cancers [ 8 ].…”
mentioning
confidence: 89%
“…A detailed description of diagnostically relevant genetic aberrations can be found in the paper by Taverna et al in this Special Issue [ 7 ]. In addition, methylation profiling has been shown to allow the classification of sinonasal tumor subtypes, even identifying subgroups of tumors within SNUC and SNEC [ 8 ]. A similar approach to aid and finetune the diagnosis of the multitudinous subtypes of brain tumors has now been implemented by the WHO Classification of Tumors [ 9 ].…”
mentioning
confidence: 99%
“…DNA methylation is the firstly recognized epigenetic alterations and it is closely connected with the development of cancer. When the promoter region of genes was methylated, the accessibility to regulatory regions in the DNA was blocked and the transcription factors or other transcriptional regulators can't bind with the promoter of genes, which lead to the repression of gene transcription ( Jurmeister et al, 2022 ). Specifically, various tumor suppressor genes (TSGs) were identified to be hypermethylated thus facilitating the development of cancer via TSGs silencing, such as BRCA1 ( Das et al, 2022 ) and CDKN2A ( Maeda et al, 2003 ).…”
Section: Epigenetic Phenomenon and Cancermentioning
confidence: 99%